Tepid sponge and sponge bath to change body temperature children with dengue fever - Hastuti, Witri; Sari, Novi Murdiana; Wulaningsih, Indah (South East Asia Nursing Research, 2020)
Dengue Haemorrhagic Fever (DHF) is a viral infection transmitted by mosquitoes causing potentially deadly complications. The typical sign of this case is getting high fever until 3-7 days then it drops quickly. To make a lower body temperature, compress the body with warm water by using tepid sponge and sponge bath techniques. The objective of this study to determine the effect of compresses with tepid sponge and sponge bath techniques on changes in children's body temperature with DHF. This study used quantitative research with quasi-experiment design two group pre-test post-test design approach. The population of 30 children with fever, with purposive sampling technique using the Lemeshow formula. The analysis used was paired T-test, Wilcoxon, and Mann Whitney at a significance level of 0.05. Wilcoxon statistical test results show there is a tepid sponge effect on children body temperature with DHF with a p-value of 0.001. The dependent t-test shows there is an influence of sponge bath in children body temperature with DHF p-value of 0,000. The Mann witney test shows that Sponge bath is more effective than a tepid sponge in reducing fever with a p-value of 0,000. The conclusion of this study can be used as a guide for treating children with fever with the issuance of a standard SPO. Application of this method needs to involve parents to maintain the comfort of children, so it needs to make socialization to parents.